Occupational performance and multisensory stimulation during post-traumatic amnesia: An observational and randomized controlled trial protocol. (October 2019) - Walsh, Hayley; Fleming, Jennifer; Silvestre Edo, Cristina; Bernabeu Guitart, Montserrat; Murillo, Narda
Background: Occupational performance (OP) and interventions during post-traumatic amnesia (PTA) following traumatic brain injury are poorly understood. Purpose: This study aims to describe a study protocol to (a) track person factors of OP throughout PTA and (b) assess the feasibility of a randomized controlled trial (RCT) protocol comparing an occupation-based multisensory stimulation and environmental enrichment intervention with usual care during PTA. Method: A prospective observational study will be conducted with an embedded Phase II RCT with 30 participants in PTA. Participants will be randomly assigned to group and regularly assessed on PTA and OP measures. Feasibility aspects will be recorded in a logbook. All measures will be repeated at PTA resolution and 1 month later, with a follow-up questionnaire completed at 6 months postinjury. Findings: Observational data will be analyzed using correlations. Feasibility will be examined descriptively, and group comparisons will be conducted to determine effect size. Implications: Results will provide a broader understanding of OP during PTA and inform future trials.